Long-Term Outcomes of the Electrically Unresponsive, Anatomically Intact Facial Nerve Following Vestibular Schwannoma Surgery - Shoakazemi, Alireza; Feria, Alejandro; Kanakis, Constantine E.; Stapleton, Emma; Pathmanaban, Omar N.; Freeman, Simon R.; Lloyd, Simon; Rutherford, Scott A.; King, Andrew Thomas; Hammerbeck-Ward, Charlotte L. (Journal of Neurological Surgery Part B: Skull Base, 2021)
Objective The study aimed to determine long-term outcomes in patients with intraoperative electrical conduction block in an anatomically intact facial nerve (FN).Methods Single center retrospective review of prospectively collected database of all vestibular schwannoma surgeries between January 1, 2008 and August 25, 2015. Operative notes were reviewed and patients with anatomically intact FNs, but complete conduction block at the end of surgery were included for analysis.Results In total, 371 patients had vestibular schwannoma surgery of which 18 met inclusion criteria. Mean follow-up was 34.28 months and average tumor size was 28.00 mm. Seventeen patients had House-Brackmann Grade VI facial palsy immediately postoperatively and one patient was grade V. At 1 year, three patients remained grade VI (17%), two improved to grade V (11%), seven to grade IV (39%), six to grade III (33%), and one patient to grade II (6%). On extended follow-up, five patients (28%) had additional 1 to 2 score improvement in facial function. Subset analysis revealed no correlation of tumor size, vascularity, adherence to nerve, operative approach, extent of resection, splaying of FN, and recurrent tumor or sporadic tumors to the extent of FN recovery.Conclusion Intraoperative conduction block does not condemn a patient to permanent FN palsy. There is potential for a degree of recovery comparable with those undergoing nerve grafting. Our data do not clearly support a policy of same-surgery or early-postoperative primary nerve grafting in the event of a complete conduction block, and instead we favor monitoring for recovery in an anatomically intact nerve.
Keywords: conduction block; vestibular schwannoma; facial nerve; electrophysiological monitoring